Pelatihan Pemanfaatan Editing Vidio Sebagai Media Dalam Pembelajaran Serta Pemasaran Berbasis Ict Dimasa Pandemi Covid-19 - Imam Mutaqin; Abu Zaini (LP3M IAIFA Kediri, 2021)
In the excitement of community service this time which was carried out in the hamlet of Sumbersari-Kencong-Kepung Kediri. Which was held for a period of 3 weeks starting from July 26, 2021 until August 26, 2021. Various KKN-DR activities start from observation, program planning, program consultation in accordance with the planned program, namely the KKN-DR activity held in the form of vidio edting training with the title